Aortic Graft Infection as a Cause of Multiple Brain Infarcts - Vassiliki Tsirka; Jelena Maletic; Panagiotis Ioannidis; Dimitrios Karacostas (Case Reports in Cardiology)
Brain embolism of cardiac origin is common in clinical practice. However, embolic brain infarcts due to aortic graft infection are very rare. We present a case of a 53-year-old woman with multiple brain infarcts, following an infection of ascending aortic graft. She was presented with fever and acute onset neurological deficit, and she had a previous history of replacement of ascending aorta with a prosthetic graft, because of aortic aneurysm 2 years before her admission. The patient had positive blood cultures and echocardiographic evidence of vegetation in the graft aortic joint, nearby the aortic valves. Despite the severe clinical condition and the poor prognosis, because of the coexistence of cardioembolism and aortic graft infection, our patient had a good outcome with conservative treatment and she will be considered for surgical graft replacement after her full recovery.